ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL CERITA MATEMATIKA BERDASARKAN ANALISIS KESALAHAN NEWMAN PADA SISWA KELAS VIII SMP NEGERI 7 PADANG - DITIA ERIKA FEBRIANI (Departemen Matematika, 2018)
The purpose of this research is to find out where the students are wrong in solving mathematical problems and to describe the factors that caused them. The type of the research is descriptive research with the subject of the research is class VIII.1 students of SMP Negeri 7 Padang. The students of class VIII.1 are 32 students.Analysis of test result uses Newman’s analysis. The result of data analysis showed that the most mistakes made by students were errors in writing the final answer with precentage of 29,83%. Errors made by students consist of, the students cannot write the context meaning of problems correctly, do not write what is known and asked, write what is known and asked but not in accordance with the request, errors in computing, misconception, write the answers until end which is not accordance with the context of the question. The factors that cause students to make mistakes include : unable to arrange the meaning of words that are thought into the form of grammatical structures, do not understand the meaning of questions, do not serious in following the lessons have given by the teacher, cannot understand information problems contained in the problem, lack of practice on the problems in the form of stories in different variations, misunderstanding information from the teacher, lack of understanding the problem, lack of understanding the material, lack of understanding the material preconditions. Keywords–error analysis, mathematical problems, Newman’s analysis